HUBUNGAN LINGKAR DADA DAN PANJANG BADAN TERHADAP BOBOT BADAN DAN PERTAMBAHAN BOBOT BADAN HARIAN DOMBA CROSSBREED DORPER - Perdana Abdi Negara, Pria; Haryoko, Imbang; Prayitno, Caribu Hadi (Universitas Bengkulu, 2024)
This research aimed to determine the relationship between chest circumference, body length, body weight and daily gain in Crossbreed Dorper sheep. The samples used were 15 male F1 Dorper sheep and 15 female F1 Dorper sheep, aged 3.5 – 4 months, with an average weight of 30.88 ±0.847kg. The survey study was conducted using a random sampling method. The variables measured were chest circumference, body length, weight, and daily gain. The results of the study show that: (1) the regression equation for chest circumference on body weight Y = 0.77+0.64 CC for Rams and Y = 2.35+0.57 CC for Ewes, (2) the regression equation for body length on body weight Y = -30.27+1.12 BL for rams and Y = -16.59+0.80 BL for ewes, (3) multiple regression equation of chest circumference and body length on body weight Y = 7, 94+ 0.75 CC - 0.21 BL for rams and Y = -4.47+0.45 CC+0.22 CC for ewes. The correlation coefficient (r) is close to +1.0, indicating that the relationship between the two variables is powerful and positive. It was concluded that the chest circumference and body length have a solid positive relationship with body weight. The body weight of Crossbreed Dorper sheep can be predicted accurately using chest circumference and body length. However, the daily gain of Crossbreed Dorper sheep cannot be estimated using chest circumference and body length because the coefficient of determination is low.